Sensing defects: Collaborative seeing in engineering work. (August 2021) - Sargent, Adam; Vinson, Alexandra H; Stevens, Reed
This paper explores how professional engineers recognize and make sense of product defects in their everyday work. Such activities form a crucial, if often overlooked, part of professional engineering practice. By detecting, recognizing and repairing defects, engineers contribute to the creation of value and the optimization of production processes. Focusing on early-career engineers in an advanced steel mill in the United States, we demonstrate how learning specific ways of seeing and attending to defects take shape around the increasing automation of certain aspects of engineering work. Practices of sensing defects are embodied, necessitating disciplined eyes, ears, and hands, but they are also distributed across human and non-human actors. We argue that such an approach to technical work provides texture to the stark opposition between human and machine work that has emerged in debates around automation. Our approach to sensing defects suggests that such an opposition, with its focus on job loss or retention, misses the more nuanced ways in which humans and machines are conjoined in perceptual tasks. The effects of automation should be understood through such shifting configurations and the ways that they variously incorporate the perceptual practices of humans and machines.